2009
DOI: 10.1007/s10532-009-9266-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inducers on the decolorization and biodegradation of textile azo dye Navy blue 2GL by Bacillus sp. VUS

Abstract: Bacillus sp. VUS decolorized azo dye Navy blue 2GL in 48 h at static anoxic condition in yeast extract medium, whereas it took only 18 h for the decolorization in presence of CaCl(2). Different inducers played role in the decolorization of Navy blue 2GL. CaCl(2) found to be the most effective inducer among all inducers tested. The activity of enzymes like lignin peroxidase, laccase and reductases viz. NADH-DCIP, azo and riboflavin induced during decolorization represents their role in the biodegradation. Extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…It is well known that bacteria degrade azo dyes reductively under anaerobic conditions to colorless aromatic amines. The carcinogenicity of an azo dye may be due to the dye itself or aryl amine derivatives produced during the reductive biotransformation of an azo linkage (Dawkar et al 2009). These colorless aromatic amines should be degraded further because these may be toxic, mutagenic, and carcinogenic to humans and animals (Chen 2006).…”
Section: Biodegradation Of Dyes By Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that bacteria degrade azo dyes reductively under anaerobic conditions to colorless aromatic amines. The carcinogenicity of an azo dye may be due to the dye itself or aryl amine derivatives produced during the reductive biotransformation of an azo linkage (Dawkar et al 2009). These colorless aromatic amines should be degraded further because these may be toxic, mutagenic, and carcinogenic to humans and animals (Chen 2006).…”
Section: Biodegradation Of Dyes By Bacteriamentioning
confidence: 99%
“…They concluded that the degradation product was less toxic. Dawkar et al (2009) carried out phytotoxicity analysis of textile azo dye Navy blue 2GL and its metabolites formed after degradation by Bacillus sp. VUS.…”
Section: Phytotoxicity and Microbial Toxicity Of Dyes And Their Biodementioning
confidence: 99%
“…Considering the time and decolorization efficiency, 24 h of treatment time is suitable for spore laccase in dye decolorization ( Figure 5d). Some Bacillus species cultures can also degrade synthetic dyes with high efficiency, but usually need a longer time than spore laccase (Dawkar et al, 2009;Kadam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several synergistic interactions of oxidoreductase-related enzymes such as laccase (EC 1.10.3.2; Dawkar et al 2009), azoreductase (EC 1.7.1.6; Maier et al 2004), and NADH dehydrogenase (EC 1.6.5.3; Ng et al 2013) or cytochrome C oxidase (Wariishi et al 2002) were involved simultaneously. These enzymes all play crucial roles in dealing with decolorization of azo dyes, suggesting that decolorization seemed not simply to be driven solely by mono enzymatic catalysis or single metabolic route.…”
Section: Genomic and Enzymes Studies Of Proteusmentioning
confidence: 99%